Evaluation of Serum Malondialdehyde, Glutathione and Lipid Profile Levels in Iraqi Females with Type 2 Diabetes Mellitus (Baghdad Science Journal, 2016)
This study is carried out on patients with type 2 diabetes mellitus to assess the lipid profile, malondialdehyde and glutathione. Our study is concerned with 51 (Iraqi Arab females) patients of type 2 diabetes mellitus compared with 31 control subjects unified in age, sex and ethnic background. Lipid profile is measured by using commercially available kits, while the serum MDA and glutathione levels are measured by means of sandwich ELISA test using commercially available kits. Serum MDA is significantly higher (P